Studies on the diversity of macrofungus in Kodaikanal region of Western Ghats, Tamil Nadu, India - BOOBALAN THULASINATHAN; MOHAN RASU KULANTHAISAMY; ARUMUGAM NAGARAJAN; SARAVANAN SOORANGKATTAN; JOTHI BASU MUTHURAMALINGAM; JEYAKANTHAN JEYARAMAN; ALAGARSAMY ARUN (Society for Indonesian Biodiversity, 2018)
Boobalan T, Mohan Rasu K, Arumugam N, Saravanan S, Jothi Basu M, Jeyakanthan J, Arun A. 2018. Studies on the diversity of macrofungus in Kodaikanal region of Western Ghats, Tamil Nadu, India. Biodiversitas 19: 2283-2293. We have demonstrated the distribution of macro fungal communities in the selected forest territory of Kodaikanal (Poondi) region, which houses about 100 mushrooms species diverse forms of mushrooms including both the soil-inhabiting (n = 45) and wood-inhabiting (n = 55) species. Kodaikanal is situated on a plateau between the Parappar and Gundar valleys; this area experiences peculiar lower temperature between 8.2°C and 19.7°C, higher humidity between 92% and 95%, which in turn enhances the growth of different types of mushrooms throughout the year. However, the peak production and macro fungal flushes were observed during the winter season followed by the northeast monsoon (Oct-Dec 2015). A total of 100 species belonging to 51 families were documented from this study sites. Moreover, some species (e.g., Ganoderma sp and Phellinus sp) persists all around the year in this region. However, some incidents of logging and burning of host trees have resulted in the decline of the macro fungal populations in this region. Hence the present study highlights the diversity of macro fungal population and also suggests their importance as part of biodiversity conservation.